Touch imprint cytology of core needle biopsy specimens for the breast and quick stain procedure for immediate diagnosis - Kehl, Sven; Mechler, Christina; Menton, Susanne; Weiss, Christel; Wasgindt, Sabine; Suetterlin, Marc; Trunk, Marcus (Anticancer Research, 2014)
To investigate the validity and reproducibility of touch imprint cytology (TIC) of core needle biopsies (CNBs) in the assessment of conspicuous breast findings.One hundred and fifty-eight conspicuous breast findings were assessed by CNB during a two-year period in this prospective study. TIC of the CNBs was used for cytological analysis. The performance of this technique was evaluated by comparing the results with the histology of the CNB, and in cases of a subsequent surgery, with the final histology. In addition, inter-observer reproducibility was analyzed.The inter-observer variability was very high (kappa-value of 0.8508; excluding inadequate imprints, 0.9502). Inadequate cellularity for cytological analysis was found in 11.4% (18/158) of findings. Compared with CNB histology, the sensitivity, specificity, positive predictive value, negative predictive value and overall accuracy of TIC was 99%, 100%, 100%, 94%, and 99%, respectively.TIC of CNB specimens of the breast may be a valid option for providing a diagnosis without delay for a histological procedure, assuming good quality of the specimen.
EVALuna2:17528